Jitter and muscle fiber conduction velocity in long COVID fatigue - Kouyoumdjian, João Aris; Yamamoto, Leticia Akemi Rama; Graca, Carla Renata (Arquivos de Neuro-Psiquiatria, 2025)
Background Long coronavirus disease (long COVID, LC) is defined as the continuation or development of new symptoms 3 months after the acute stage of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In LC, the rate of fatigue/postexertional malaise (F-PEM) has been described to be as high as 70%, regardless of age or severity of the acute symptoms.Objective To evaluate the neuromuscular junction (NMJ) function and the isolated muscle fiber conduction velocity (MFCV) in situ in LC cases and controls.Methods We studied 37 subjects without SARS-CoV-2 (controls) and 32 cases of SARS-CoV-2 infection, half with LC symptoms (LC-yes) and half without them (LC-no). Single-fiber electromyography (jitter measured with a concentric electrode), MFCV, the fast-to-slow MFCV ratio (F/S ratio), and the motor unit potentials (MUPs) were taken in the tibialis anterior muscle.Results At least 1 jitter parameter was abnormal in 1/37 controls, in 1/16 LC-no patients, and in 2/16 LC-yes patients, without significant differences among them. None of the subjects with abnormal jitter presented fluctuation symptoms or positive acetylcholine-receptor antibody. The MFCV and F/S ratios did not show abnormalities in any of the participants. The MUPs did not show myopathic or neurogenic abnormality in needle electromyography. The most frequent symptom in LC was F-PEM, which occurred in all LC-yes patients and was significantly different from the other groups.Conclusion Fatigue/postexertional malaise was found in all cases of LC, and the electrophysiological findings did not indicate the muscle fiber or the NMJ as a relevant factor in this condition.
Keywords: SARS-CoV-2; Post-Acute COVID-19 Syndrome; Fatigue; Single-Fiber Electromyography; Muscle Fiber Conduction Velocity